Oneeha coastal mangrove restoration: A climate adaptation strategy - Rembah, Rina; Rustan, Fathur Rahman; Salu, Sahrul Poalahi; Suwarto, Suwarto; Arif, Arif; Hasriyanti, Hasriyanti; Nurfasiha, Nurfasiha; Kumalasari, Rizki; Yatjong, Isramyano; Syahrul, Syahrul; Dzakir, La Ode; Murdiansyah, Eko Bambang; Nursyafika, Nursyafika; Renaldi, Ahmad; Zakina, Besse Ririn (Universitas Muhammadiyah Magelang, 2025)
The intensification of climate change is having serious impacts on coastal areas. Mangrove restoration at Oneeha Beach is a crucial effort to enhance the resilience of the coastal ecosystem while also empowering the socio-economic well-being of the local community. This program actively involved the community in the planting and maintenance of mangroves, as well as socialization and education activities on the importance of this ecosystem. The results of the activities demonstrated a significant increase in community environmental awareness, understanding of the technical aspects of mangrove planting and conservation, and the successful planting of new mangrove seedlings in degraded coastal areas.